Единожды солгавший: повесть и рассказы / Татара Крюкова - Крюкова Тамара Шамильевна (Современная проза, 2023)
Экземпляры: аб. ЦБ (20240527) / Инвентарный номер: 19333 / Цена: / Авт.знак: К 85 / ББК: 84(2=411.2)6